Delivery Outcome After Trial of Labor in Nulliparous Women 40 Years or Older: A Nationwide Population-based Study. Issue 2 (June 2020) - Ankarcrona,; Altman, D.; Wikström, A.; Jacobsson, B.; Wendel, S.B.
Abstract : ( Acta Obstet Gynecol Scand . 2019; 98:1195–1203) Over the last 3 decades, more and more women in high-income countries have postponed childbirth until the age of 40 or older. Women of advanced maternal age are more likely to undergo labor induction, which may be associated with risk of labor complications, such as intrapartum cesarean delivery and adverse neonatal outcomes. Therefore, obstetricians are unsure how to advise nulliparous women 40 years or older on labor and delivery method. These investigators conducted their study to compare delivery mode and risks of anal sphincter injury and 5-minute Apgar score <7 in older women (40 y or older) compared with women 25 to 29 years old for both labor induction and spontaneous onset of labor.